2003
DOI: 10.1136/oem.60.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relations between exposure to respirable quartz and risk of silicosis

Abstract: Aims: To reanalyse exposure-response data from a Scottish colliery to gain a more detailed knowledge of the relations between exposure to quartz and risks of silicosis in coal miners, and hence inform the debate on an appropriate occupational standard for respirable quartz. Methods: Detailed data on working times at different quartz concentrations were combined to produce exposure profiles for miners who had provided a full chest radiograph at a follow up survey. Logistic regression methods were used to model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 18 publications
3
65
0
4
Order By: Relevance
“…In contrast, the Institute of Occupational Medicine (IOM) study on Scottish coal-miners (Buchanan D, Miller and Soutar, 2001) demonstrated a curvilinear (quadratic-like relationship) between silica exposure and silicosis risk (as assessed by radiological tests). Using those data, the ratio of silicosis cases to lung cancer cases was 2:1.…”
Section: Mesothelioma -Asbestosmentioning
confidence: 95%
“…In contrast, the Institute of Occupational Medicine (IOM) study on Scottish coal-miners (Buchanan D, Miller and Soutar, 2001) demonstrated a curvilinear (quadratic-like relationship) between silica exposure and silicosis risk (as assessed by radiological tests). Using those data, the ratio of silicosis cases to lung cancer cases was 2:1.…”
Section: Mesothelioma -Asbestosmentioning
confidence: 95%
“…Nevertheless, occupational studies can help to estimate potential 643 threats from Sakurajima ash. Chronic diseases generally only occur after years of exposure 644 on an almost daily basis and with high concentrations of respirable crystalline silica (AIOH 645 2009), although short-term, very-high exposures may be more hazardous than equivalent 646 exposures at lower levels over longer timescales (Buchanan et al 2003). Some recent studies 647 have highlighted that risk from crystalline silica may have been underestimated, with 648 27 reported cases of silicosis in people working within legal exposure limits (Park et al 2002).…”
mentioning
confidence: 99%
“…Hnizdo et al have indicated that the relationship between the risk of silicosis and the dose up to 4 mg/m 3 ×years is linear; at higher doses, the risk of silicosis increases in a manner similar to an exponential function (18). Multiple increase in the risk was also noted for the doses exceeding 2 mg/m 3 ×years followed by additional several months of exposure to crystalline silica at concentrations higher than 2 mg/m 3 (20). Yet another factor increasing the risk of developing silicosis consists in the exposure to freshly fractured silica dusts produced during crushing, grinding or pulping siliceous materials (3,33).…”
Section: Methodsmentioning
confidence: 99%